ANALISIS PENGARUH PERSEPSI PERAWAT PELAKSANA TENTANG FUNGSI MANAJERIAL KEPALA RUANG TERHADAP PENDOKUMENTASIAN ASUHAN KEPERAWATAN DI RUANG RAWAT INAP RUMAH SAKIT SWASTA DI SEMARANG - Haryanti, Tri; Pujianto, Tri Ismu; Adinatha, Ni Nyoman (Jurnal Manajemen Keperawatan, 2013)
Background: This research background by a management function has not been a good head space as functions of planning, organizing, directing, monitoring and controling. Nursing management is the coordination and integration of nursing resources by applying the management process to achieve the goal, objectivity nursing care and nursing services. Good managerial function in nursing management is critical nursing care in the inpatient nurse practitioner in carrying out documentation of nursing care to clients. Purpose: This study aims to analyze the effect of implementing the nurses perception of the function manjerial head space of the implementation of documenting nursing care in the inpatient hospital nursing Wilasa Citarum Semarang. Methods: The method of research is a kuantitatif study with cross â sectional study. The research population is 57 nurse practitioner in the inpatient Orchid lounge, Cempaka, Dahlia and Flamboyan. Results: The result shows the perception of the nurse practitioner about managerial functions well enough head room (68.4%), the implementation of good documentation of nursing care (42.1%). Conclusion: a relationship between the perception of the nurse practitionerabout managerial function head space of the implementation of nursing documentation in patient wards (p = 0027).